Osteomyelitis is Commonly Associated With Septic Arthritis of the Shoulder in Children. Issue 8 (December 2017) - Ernat, Justin; Riccio, Anthony I.; Fitzpatrick, Kelly; Jo, ChanHee; Wimberly, Robert L.
Abstract : Purpose: To describe the clinical presentation, management, and outcomes of surgically treated septic arthritis of the shoulder in a pediatric population. Methods: A retrospective chart review over 5 years of children with operatively managed septic arthritis of the shoulder was completed. Demographics, clinical presentation, symptoms duration, antibiotic regimen and duration, number of surgical procedures, and evaluation of laboratory value improvements were collected. Pretreatment and final radiographs were assessed. Causative organisms were reviewed. Patients were stratified in age groups to determine clinical variability based upon patient age. Results: A total of 22 children, ages 15 days to 14 years (average 37.3 mo), were treated for septic arthritis of the shoulder from 2006 to 2010 at a single pediatric institution. All patients were managed with open anterior arthrotomy at an average of 1.95 days after initial orthopaedic consultation (range, 0 to 15 d). Multiple presenting signs were noted; the most common was decreased use (59%). Average admission laboratory values include C-reactive protein 10.6 (range, 0.3 to 41.6), erythrocyte sedimentation rate 62.8 (range, 11 to 107), and white blood cell count 14.9 (range, 5.9 to 31.7). Initial radiographs were read as normal in 12 patients, concern for osteomyelitis in 5, cortical irregularity in 4, effusion in 3, and neoplasm in a single child. Nineteen patients had a preoperative magnetic resonance imaging and 15 demonstrated an effusion, 15 had evidence of humeral osteomyelitis, 5 had a subperisoteal abscess, and 4 had soft tissue abscesses. Eight patients remained culture negative. The most commonly identified organism was methcillin-resistant Staphylococcus aureus (MRSA) (22.7%). The patients under 12 months of age revealed more diverse organisms at culture and were less likely to have MRSA. All patients averaged 1.55 (range, 1 to 5) surgical procedures and had an average hospital stay of 13.5 days. Intravenous antibiotics averaged 16.3 days followed by an average of 34 days of oral treatment. MRSA patients were significantly more likely to require multiple operations to eradicate the infection ( P <0.02) and had a longer duration of intravenous antibiotic use ( P <0.003). MRSA patients were more likely to have abnormal radiographs at final follow-up ( P <0.03). Conclusions: Septic arthritis of the shoulder in children is commonly associated with adjacent osteomyelitis. Pediatric septic arthritis of the shoulder due to MRSA bacteria can have a more virulent course than other bacterial causes, but is a less commonly identified organism in the youngest patients. Significance: To our knowledge, this is one of the largest series published concerning the treatment, course, and outcomes of pediatric septic arthritis of the shoulder. Level of Evidence: Level III—therapeutic.